2016
DOI: 10.1167/iovs.15-17478
|View full text |Cite
|
Sign up to set email alerts
|

Myopes Show Greater Visually Induced Postural Responses Than Emmetropes

Abstract: PURPOSE. The literature already establishes that vision plays a crucial role in postural control and that this visual dependence shows intra-and interindividual variability. However, does ametropia also have an effect on postural control? This question leads to our study, which aims primarily to determine if myopes and emmetropes behave differently in terms of postural control when subjected to visual stimulation, and secondarily, if this difference persists in the presence of barrel and pincushion distortions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Several other risk factors have been identified as contributing towards VMH in isolated studies. These include cerebral palsy (Yu et al 2018 , 2020 ), lower back pain (Li et al 2014 ), myopia (Sayah et al 2016 ), otitis media (Casselbrant et al 1998 ), and stroke (Bonan et al 2013 ; Yelnik et al 2006 ). These studies found respective patient group to exhibit increased postural sway during visual motion.…”
Section: Resultsmentioning
confidence: 99%
“…Several other risk factors have been identified as contributing towards VMH in isolated studies. These include cerebral palsy (Yu et al 2018 , 2020 ), lower back pain (Li et al 2014 ), myopia (Sayah et al 2016 ), otitis media (Casselbrant et al 1998 ), and stroke (Bonan et al 2013 ; Yelnik et al 2006 ). These studies found respective patient group to exhibit increased postural sway during visual motion.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on the effect of corrected vision on postural stability, Bae et al (2020) found that the static postural stability of uncorrected visual acuity (without glasses) was significantly lower than that of the corrected state. People with myopia were more unstable than those with emmetropia in terms of visual-evoked postural response ( Sayah et al, 2016 ). When myopia progresses to a certain extent, it causes blurring of visual information and decreases contrast sensitivity and stereoscopic perception ( Ikuno, 2017 ), which leads to a decline in postural stability.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia was also significantly higher than corrected visual acuity in the middle- and high-frequency spectral energy of the somatic system. Sayah et al (2016) found that people with myopia were more unstable than those with emmetropia in terms of visually induced postural responses. The postural stability includes both static and dynamic aspects, and testing static stability alone cannot fully explain the characteristics of postural stability in people with myopia.…”
Section: Introductionmentioning
confidence: 97%
“…Paulus et al [14] reported an increase in postural instability of about 25% increase due to myopic blur induced by +4.0 D and +6.0 D lenses and a similar finding in subjects with myopic refractive error between—3.0 and—5.0 D without wearing of corrective spectacles. Recently, Diane et al investigated the effects of optical distortion (Plano, pincushion of +10% and barrel of -10% distortion) on postural stability in myopes and emmetropes, and reported that peripheral dynamic visual stimuli was a more important factor influencing the posture of myopes versus that of emmetropes in both plano and barrel of -10% distortion [15]. Many previous studies demonstrated that refractive error significantly interfered with postural stability [13,14,16,17], but those studies had the limitation of inability to calculate the minimum refractive power that degrades postural stability; Moreover, although hyperopia is a common type of refractive error, most of those studies focused only on myopic blur [13,14,16,17].…”
Section: Introductionmentioning
confidence: 99%